2012
DOI: 10.1002/crat.201200147
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the blue photorefractive properties varied with MgO codoping in Ru:Fe:LiNbO3 crystals

Abstract: Mg:Ru:Fe:LiNbO3 crystals with various doping concentration of MgO have been grown by Czochralski method. The type of charge carriers and photorefractive properties in Mg:Ru:Fe:LiNbO3 crystals were measured by two‐wave coupling method using Kr+ laser (476 nm) and He‐Ne laser (633 nm) as light sources. We found that holes were the dominant charge carriers under blue light irradiation while electrons were the dominant charge carriers under red light irradiation. Mg2+ ions behaved no longer as damage resistant, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…[18] Here, holes are the dominant charge carriers under blue exposure. [19] It is found that the blue light is short enough to excite holes both in the shallow and deep trap centres, thus a grating can be directly recorded into the two centres. The repeating cycles of holes excitation-transport-trapping between shallow trap centre and deep trap centre are prohibited, therefore the sensitivity is enhanced compared with that in the conventional two-colour recording.…”
Section: Nonvolatile Holographic Storagementioning
confidence: 99%
“…[18] Here, holes are the dominant charge carriers under blue exposure. [19] It is found that the blue light is short enough to excite holes both in the shallow and deep trap centres, thus a grating can be directly recorded into the two centres. The repeating cycles of holes excitation-transport-trapping between shallow trap centre and deep trap centre are prohibited, therefore the sensitivity is enhanced compared with that in the conventional two-colour recording.…”
Section: Nonvolatile Holographic Storagementioning
confidence: 99%
“…Thus, based on the considerations above, two-center Sc:Ru:Fe:LiNbO 3 crystals were grown using the Czochralski method. The incident light wavelength was selected as 476 nm (blue light), which has enough energy to excite the charge carriers' holes of the Sc:Ru:Fe:LiNbO 3 crystals [18]. It was established experimentally that the blue photorefraction of the Ru:Fe:LiNbO 3 doped with Sc was enhanced significantly compared to Sc:Ru:Fe:LiNbO 3 crystals.…”
Section: Introductionmentioning
confidence: 99%